YIELD PERFORMANCE OF POTATO CULTIVARS AGAINST ARSENIC CONTAMINATION - Haque, Md. Nazmul; Ali, Md. Hazrat; Roy, Tuhin Suvra (Potato Journal, 2016)
Arsenic (As) contamination often affects the yield of potato tubers. In this study, therefore, yield contributing parameters of 14 potato cultivars in Bangladesh viz., ‘Diamant’, ‘Cardinal’, ‘Asterix’, ‘Granola’, ‘Lady Rosetta’, ‘Courage’, ‘BARI TPS-1’, ‘Meridian’, ‘Felsina’, ‘Laura’, ‘Quincy’, ‘Sagitta’, ‘Rumana’ and ‘Jam Alu’ were examined. The different levels of As had significant effect on most of the yield contributing characters of potato cultivars. All the parameters studied in this experiment were decreased with the increasing As levels except number of tubers/hill, non-marketable yield/plant, 28-45 mm and <28 mm sized tuber. The yield of potato cultivars negatively affected by As contamination. The variety ‘Felsina’ produced maximum yield/plant (426.2 g) whereas, ‘Jam Alu’ showed minimum yield/plant (77.15 g) irrespective of As levels. The results showed yield/plant, average tuber weight, large and medium sized tubers were decreased with the increasing As levels but remained statistically similar up to 25 mg As/kg soil and thereafter drastically decreased. Among the treatment combinations, ‘Felsina’ grown with 0 mg As/kg soil performed the best results and the same variety with 25 mg As/kg soil also showed the statistically similar results in terms of most of the yield contributing parameters.